Noninvasive Detection of Trophoblast Protein Signatures Linked to Early Pregnancy Loss using TRIC - Fritz, Rani (Fertil Steril, 2015)
OBJECTIVE: To examine the expression pattern of biomarker proteins in extravillous trophoblast (EVT) cells obtained noninvasively by transcervical retrieval and isolation from the cervix (TRIC) in patients with early pregnancy loss, compared to control patients with uncomplicated term delivery. DESIGN: Case-control study. SETTING: Academic medical center. PATIENTS: Endocervical specimens were obtained from ongoing pregnancies at gestational ages of 5 to 10 weeks to generate an archive of EVT cells isolated by TRIC. INTERVENTIONS: Medical records were examined to select specimens from patients with either early pregnancy loss (EPL; N=10) or an uncomplicated term delivery (N=10), matched for gestational age at the time of endocervical sampling. MAIN OUTCOME MEASURES: Known serum biomarkers for adverse pregnancy outcome that are expressed by EVT cells were evaluated by semi-quantitative immunocytochemistry, using antibodies against endoglin (ENG), FMS-like tyrosine kinase-1 (FLT-1), alpha-fetoprotein (AFP), pregnancy-associated plasma protein-A (PAPPA), galectin-13 (LGALS13), galectin-14 (LGALS14), and placental growth factor (PGF). RESULTS: EVT purity was over 95% in all specimens, based on chorionic gonadotropin expression; however, the number of EVT cells obtained was significantly lower in women with EPL than the control group. There was significant elevation of AFP, ENG, and FLT-1, and significant reduction of PAPP-A, LGALS14, and PGF in the EPL group, compared to controls. CONCLUSIONS: In this pilot study, EVT cells isolated by TRIC early in gestation exhibit altered protein expression patterns prior to EPL, compared to uncomplicated term pregnancies.